The Integrity Of Science From The Perspective Of Islamic Fiqh Studies: A Literature Review - Hazani; Haris Riadi; Suheryeni; Maulana Ansori; Rizki Arzi Wahyuda (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
Scientific integrity has become an increasingly urgent issue in contemporary academia due to the rise of ethical violations such as data manipulation, plagiarism, and the misuse of technology. This article examines scientific integrity from the perspective of Islamic fiqh through a systematic literature review of classical and contemporary scholarly sources. Departing from dominant value-neutral approaches, the study conceptualizes knowledge (?ilm) in Islam as a moral and spiritual mandate (am?nah) that entails ethical accountability before God and society. Islamic fiqh and u??l al-fiqh provide a comprehensive framework integrating revelation, rational inquiry, and empirical observation in guiding scientific conduct. The study finds that scientific integrity in Islamic fiqh is rooted in core principles such as honesty (?idq), accountability (am?nah), justice (?adl), and public benefit (ma?la?ah), which are further reinforced by the objectives of Islamic law (maq??id al-shar??ah). This framework challenges value-neutral approaches to science by emphasizing ethical intentionality and societal impact. Distinct from general studies of scientific ethics that focus primarily on procedural norms or professional codes, this article contributes a fiqh-based scientific integrity model that systematically integrates epistemological validity, moral intention, and maq??id-oriented social responsibility into a unified normative framework. Ultimately, the fiqh-based perspective offers a holistic model for fostering ethical scientific practices that contribute to both academic credibility and the moral well-being of society.